Search for a light pseudoscalar Higgs boson produced in association with bottom quarks in pp collisions at √s=8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2017)
A search for a light pseudoscalar Higgs boson (A) produced in association with bottom quarks and decaying into a muon pair is reported. The search uses 19.7 fb−1 of proton-proton collisions at a center-of-mass energy of 8 TeV, collected by the CMS experiment. No signal is observed in the dimuon mass range from 25 to 60 GeV. Upper limits on the cross section times branching fraction, σ(pp → bbA) ¯ B(A → µµ), are set.